Role of Water on the Activity of Magnesium Silicate for Transesterification Reactions. Issue 12 (1st June 2017) - Lin, Longfei; Cornu, Damien; Mounir Daou, Maya; Domingos, Cyril; Herledan, Virginie; Krafft, Jean‐Marc; Laugel, Guillaume; Millot, Yannick; Lauron‐Pernot, Hélène
Abstract: This study aims to reveal how water adsorbed on to a solid can influence its catalytic properties for transesterification in liquid phase. A commercial magnesium silicate was subjected to a range of thermal pretreatments and used for the transesterification of ethyl acetate with methanol. Conversion of ethyl acetate decreased with increasing pretreatment temperature, in direct relation to the release of the water content of the magnesium silicate. Thermogravimetric analysis, diffuse reflectance infrared Fourier transform (DRIFT), and 1 H NMR spectroscopies revealed that physically adsorbed water had little influence on the reactivity. The water incorporated within the catalysts, however, which desorbs at higher temperatures, played a key role on the conversion. Calorimetry, in situ DRIFT spectroscopy, and 1 H NMR characterization indicate that two kinds of active site exist. These are created from the water coordinated to magnesium located on the edge of the clay‐like particles or in the defects present in the silicate layer, respectively. Their role could be to stabilize methanol deprotonated by basic Mg‐OH groups, activate the ester, or help the departure of the alkoxyl moiety. Abstract : When magnesium gets wet ! Two kinds of active sites exist that are created from the water coordinated to magnesium located on the edge of the clay‐like particles or in the defects present in the silicate layer, respectively, which could stabilize methanol deprotonated by basic Mg‐OH groups, activate ester or help the departure of the alkoxyl moiety.